Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering

Comparison of sodium zirconium phosphate and calcium zirconium phosphate structures for the retention of fluoride - Dey, Ambarish; Das Gupta, Amit; Basu, Debrata; Ambashta, Ritu D.; Wattal, P. K.; Kumar, Sanjiv; Body, Monique; Rajamohanan, P. R. (Journal of Radioanalytical and Nuclear Chemistry, 2014)
Fluoride anion interaction has been explored for the first time to investigate how the structure of sodium zirconium phosphate (NZP) and calcium zirconium phosphate (CZP) can be altered in its presence. Different compositions were made by adding NaF and CaF2 in CZP and NZP matrices respectively. Fluoride interaction differs with NZP and CZP structure as suggested by F-NMR data. The addition of fluoride to the NZP or CZP structure enables to stabilize the structure at a low temperature of 600-700 A degrees C under microwave conditions.
Keywords: F-NMR; Fluoride characterization; Microwave; NZP; PIGE